DIVERSIFIKASI, KEPEMILIKAN MANAJERIAL DAN NILAI PERUSAHAAN - , Rahayu Kusumaningsih, SE. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims at examining the effect of diversification and managerial ownership on corporate value. Data used in the study were the secondary data originating from financial statements and stock exchange data from 2004 to 2008. Sample of the study was collected using a purposive sampling technique, i.e. the collection of sample with a certain criteria in accordance with the objective of study. The criteria were that (1) the firms are manufacture companies listed in the Indonesia Stock Exchange from 2004 to 2008